2017
DOI: 10.1007/s11250-017-1301-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of vanishing of maternally derived antibodies of Ungulate protoparvovirus 1 suggests an optimal age for gilts vaccination

Abstract: The prevention of Ungulate protoparvovirus 1 (UPV1) infection and consequently the reproductive losses is based on vaccination of all pigs intended for breeding. As maternally derived antibodies (MDA) can interfere with the development of immunity following vaccination, it is important to know the duration of anti-UPV1 MDA to determine the optimal age for the best vaccination efficacy. To elucidate the association between dam and piglet antibody levels against UPV1 and to estimate the decrease rate of MDA, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…The low prevalence of PPV1 in pigs can be explained by the common vaccination of sows against parvovirosis and the passive immunity of their progeny. However, persistence of maternally derived antibodies may vary significantly, from 9 to 22 weeks [40,41,42,43]. Moreover, Foerster et al [44] showed that PPV1 can be detected in body excretions, such as feces and nasal discharge, from vaccinated sows from the 9th day post PPV1 inoculation, for at least 49 days.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of PPV1 in pigs can be explained by the common vaccination of sows against parvovirosis and the passive immunity of their progeny. However, persistence of maternally derived antibodies may vary significantly, from 9 to 22 weeks [40,41,42,43]. Moreover, Foerster et al [44] showed that PPV1 can be detected in body excretions, such as feces and nasal discharge, from vaccinated sows from the 9th day post PPV1 inoculation, for at least 49 days.…”
Section: Discussionmentioning
confidence: 99%
“…The interference of the maternally transferred immunity (MDI) against any vaccine can be described as a blocking of the antigen by the circulating antibodies or by other components, presumably cell mediated, acquired through colostrum. This is well understood for other swine infectious diseases like Aujeszky Disease virus (ADV) [38], Classical Swine Fever virus [39], Influenza A virus (IAV) [40] or Swine Parvovirus [41]. For example, pigs with significant IAV-specific MDA titres can have suppressed adaptive antibody responses to homologous infection or vaccination [40, 42].…”
Section: Discussionmentioning
confidence: 99%
“…However, the depletion of the maternally acquired antibodies is a normal phenomenon that determines when vaccination of pigs can be carried out in order for it to be effective as vaccination at a high level of maternal antibodies brings about negative interference (Truyen and Streck, 2012). An appropriate timing has been recently determined to be after three months of age for a gilt to be inseminated prior to five or six months old (Gava et al, 2017).…”
Section: Prevention and Control Of Ppv1 Infectionmentioning
confidence: 99%